2018
DOI: 10.3390/min8030083
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Toxic Elements and Their Removal via the Preparation of High-Uranium Coal in Southwestern China

Abstract: High-uranium (U) coal is the dominant form of coal in Southwestern China. However, directly utilizing this resource can also harm the environment because this element is radioactive; it is, therefore, necessary to clean this kind of coal before burning. This research studied the geochemistry of toxic elements and their partitioning during the preparation of high-U coal in China. The results show that high-U coals are mainly distributed in Southwestern China and are characterized by a high organic sulfur (S) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The fine‐grained pyrite is partly disseminated (speckles) in collotelinite (Figure c), but another part of fine‐grained pyrite occurs in fusinite coexisting with clay minerals (Figure d). Duan et al found that U occurs in fine‐grained pyrite, clay minerals, and anatase, which coexists with fine‐grained pyrite or clay minerals. In addition, U is also associated with organic component .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fine‐grained pyrite is partly disseminated (speckles) in collotelinite (Figure c), but another part of fine‐grained pyrite occurs in fusinite coexisting with clay minerals (Figure d). Duan et al found that U occurs in fine‐grained pyrite, clay minerals, and anatase, which coexists with fine‐grained pyrite or clay minerals. In addition, U is also associated with organic component .…”
Section: Resultsmentioning
confidence: 99%
“…Duan et al found that U occurs in fine‐grained pyrite, clay minerals, and anatase, which coexists with fine‐grained pyrite or clay minerals. In addition, U is also associated with organic component . These fine‐grained minerals are difficult to be liberated from coals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations